ANALYSIS OF VERBAL AND NON-VERBAL COMMUNICATION IN BARACK OBAMA’S FAREWELL ADDRESS SPEECH - Safitri, Riza; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This research discusses verbal and non-verbal communication in Barack Obama's farewell address speech. The aim was to find out verbal and nonverbal communication, kinds of verbal and nonverbal communication and how the verbal affects the no-verbal itself in Barak Obama's farewell address speech. The research was conducted using qualitative research methods. This study uses verbal theory from Adler and Rodman (2006) which divides verbal into two types, namely speech and writing, while he also uses non-verbal theory from Ruben and Stewart (2014) which groups non-verbal into five parts, namely: paralanguage, kinesics, haptics, proximity and chronemics. Kinesics refers to the body language used and facial expressions, Haptics refers to touch given such as shaking hands, etc., and Paralanguage refers to vocal or how to speak. Proxemics refers to how we interact with others; we usually talk more intimately with those who are closest to us. Two-way conversation or turns of speech are referred to as chronemics. However, in the last speech Barack Obama used only a few of the above types of non-verbal.